2015
DOI: 10.1007/s12094-015-1425-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of TP53 (R72P) and MDM2 (T309G) polymorphisms in breast cancer patients

Abstract: Our finding suggests that TP53 (Arg72Pro) polymorphism may play a significant role as risk factor for breast cancer in north Indian breast cancer patients. While MDM2 (T309G) polymorphism may not be directly associated with the risk of breast cancer occurrence in the same population, but it may play role in disease progression by triggering TP53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…Similarly, Tp53 Pro allele has been found to be associated with BC risk in North Indian [23], Austrian [22], Bangladeshi [28], Iranian [21], Turkish [30], Spanish [32], Swedish [26], American [34], German [33], Russian [36], Japanese [25], and Slovakian [35] populations. In addition, a meta-analysis performed by Gonçalves et al [31], involving 25629 BC cases and 26.633 controls from 41 studies, reported an increased BC risk due to TP53 Pro allele dominant model, but not among Asian subgroup where the risk was associated with TP53 Arg allele and the Arg dominant model.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tp53 Pro allele has been found to be associated with BC risk in North Indian [23], Austrian [22], Bangladeshi [28], Iranian [21], Turkish [30], Spanish [32], Swedish [26], American [34], German [33], Russian [36], Japanese [25], and Slovakian [35] populations. In addition, a meta-analysis performed by Gonçalves et al [31], involving 25629 BC cases and 26.633 controls from 41 studies, reported an increased BC risk due to TP53 Pro allele dominant model, but not among Asian subgroup where the risk was associated with TP53 Arg allele and the Arg dominant model.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, rs1800372 is associated with poor outcome in primary breast cancer (47), and synonymous variants in the mouse Trp53 gene have been shown to influence binding of the Trp53 transcript to MDM2 and subsequent p53 function (48). Similarly, the R72P p53 variant (rs1042522), which is not classified as a deleterious mutation, has also been implicated in cancer susceptibility in humans (49). To our knowledge, this analysis is the first multi-omics analysis of SMNs and determination of germline TP53 variants in survivors of pediatric malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain the stability of the meta-analysis after the non-inclusion of deviant studies of HWE and sensitivity analysis, we evaluated the influence of each study on pooled OR. After the exclusion of studies [39][40][41][42], no study has shown a significant influence of the pooled OR effect in each of the different genetic models ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This bias existed in mostly studies whose distribution of Arg/Arg, Arg/Pro and Pro/Pro genotypes in controls was not in HWE [59][60][61][62][63][64][65][66][67][68][69][70][71][72].We also performed an in-depth sensitivity analysis by removing each single study from the pooled data and the results showed that there was no influence of the individual data on the overall results. In addition, we also calculated the overall combined OR on the additive model (Pro vs Arg) with and without the four studies which influenced the values of the Odds ratio [39][40][41][42], and in both cases, we found that the Pro allele was associated with a high risk of developing breast cancer. The major advantage of this meta-analysis was the inclusion of a large number of samples including very selective criteria.…”
Section: Discussionmentioning
confidence: 99%